2010
DOI: 10.1051/forest/2010010
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in architectural seedling traits of Patagonian cypress natural populations from the extremes of a precipitation range

Abstract: • Species distributed along wide environmental ranges are expected to be either plastic or adapted to local optima. The elucidation of which of these alternatives prevails, is crucial in planning breeding and conservation strategies for not yet domesticated species. Austrocedrus chilensis (Cupressaceae) is the most commercially important conifer of the temperate forests of Argentina and the target of a domestication program. A steep precipitation gradient characterizes its Argentinean range. • Variation within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
1
7
0
1
Order By: Relevance
“…This supports the idea of an isolation ("isolation by wind", Gallo and Pastorino, 2010) and genetic drift effect on the considered traits in these small populations. In fact, our findings confirm previous reports in other quantitative traits (Aparicio et al, 2010;Pastorino et al, 2010) and also in neutral markers (Pastorino and Gallo, 2009;Arana et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…This supports the idea of an isolation ("isolation by wind", Gallo and Pastorino, 2010) and genetic drift effect on the considered traits in these small populations. In fact, our findings confirm previous reports in other quantitative traits (Aparicio et al, 2010;Pastorino et al, 2010) and also in neutral markers (Pastorino and Gallo, 2009;Arana et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…These steps are now in progress. Several contributions have already been made (Aparicio et al , 2012; Pastorino et al ), and others have studies underway.
The definition of only two seed transfer zones for Patagonian cypress in its Argentinean range is not enough to preserve the genetic identity of its natural populations. At least five seed transfer zones must be delineated in order to avoid the risks of genetic contamination and maladaptation in active restoration programs. Isozymes are a useful tool for the characterization of the pattern of genetic diversity of Patagonian cypress, which can contribute to the delineation of operational genetic management units such as seed transfer zones, but an analysis of genetic control of the zymograms is necessary for reliable data.
…”
Section: Discussionmentioning
confidence: 99%
“…These steps are now in progress. Several contributions have already been made (Aparicio et al 2010(Aparicio et al , 2012Pastorino et al 2010), and others have studies underway.…”
Section: Discussionmentioning
confidence: 99%
“…However, under current assumptions of changing climates, relaxing these guidelines may be appropriate (Millar et al 2007). Expanding seed zone sizes and admixture of germplasm from adjacent zones might be considered, particularly in species such as Austrocedrus that demonstrate at least some degree of phenotypic plasticity (Gyenge et al 2005; Pastorino et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Little genetic structure was documented in a previous study employing isozymes ( F ST = 0.060) (Pastorino & Gallo 2009). Although, relatively high phenotypic plasticity was suggested for morphological traits (Gyenge et al 2005; Pastorino et al 2010), and genetically controlled differences driven by temperature were found in cuticular lipids (Dodd & Afzal‐Rafii 2000). At the level of individual populations, relatively high isozyme and microsatellite diversity was detected in eastern Austrocedrus populations, which was interpreted as survival in local refugia during ice ages (Pastorino & Gallo 2009; Arana et al 2010).…”
Section: Introductionmentioning
confidence: 99%